The Influence of Spiritual Guided Imaginary on Anxiety to Hemodialysis Patients in The Syarifah Ambami Ratu Ebu Bangkalan Regional General Hospital - Nur Arifah, Ninuk; Yusuf, Ah.; Kartini, Yanis (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
Chronic kidney failure is an abnormality or damage to the structure and progressive and irreversible kidney function that must undergo hemodialysis to improve their life sustainability. Most hemodialysis patients experience anxiety because they have to undergo hemodialysis therapy for the rest of their lives This study aims to determine the effect of spiritual guided imagery on anxiety in hemodialysis patients at Syarifah Ambami Ratu Ebu Bangkalan Hospital. The research design used in this study was Quasy-Experimental with a pre and post test control group design approach. The sample in this study were 44 respondents, 22 intervention groups and 22 control groups, using the Simple Samples technique of Random Random Sampling. The technique used was the lottery technique. Data was collected using a questionnaire. The analysis was carried out using a Manova test with a 95% confidence interval (α = 0.05). The results of statistical tests using the Manova test showed that there was an influence of spiritual guided imagery on anxiety in hemodialysis patients with p value = 0.000. Hemodialysis patients who experience anxiety can be given non-pharmacological therapy in the form of spiritual guided imagery because it has been proven to reduce anxiety and this therapy is easy to apply.